Análise da temperatura do ar utilizando a teoria da complexidade em floresta de transição no norte de Mato Grosso - Silva, Hozana (2014)
The aim of study was to study the air temperature behavior using complexity theory in transition forest in Sinop Mato Grosso State. Evaluate the relationship between the attractors reconstructed and the seasons, influence of cold fronts and subsequent variables that modify the patterns of air temperature. The data include the years 2001, 2002, 2003 and 2007. The statistical analysis was performed with chi - square test (x2) checking the hourly average values represent the experimental data for months. Soon the Amazon rainforest has been considered important ecosystem in control of the local climate. With the large-scale deforestation, may notice changes in the local climate. Therefore, Complexity Theory is needed to understand the Amazon rainforest because it is a complex environment where your variables influence each other not obeying a linearity thus transmitting to the inherent uncertainty and unpredictability. With this condition, it is necessary a study more dup that this ecosystems behavior of the Amazon rainforest. For a better understanding of the environmental variables predictability, likes air temperature, it is necessary a study of this variable in certain periods, thus verifying the difficulties in providing for them and a possible effect of seasonality. One way to conduct this study is the reconstruction of attractors, based on the Theory of Complexity.